OP0220 SINGLE-CELL TRANSCRIPTOMIC AND FUNCTIONAL ANALYSES REVEAL NOVEL HETEROGENEITY IN PATHOGENIC PATHWAYS MEDIATED BY HUMAN SYNOVIAL TISSUE MACROPHAGES. (June 2019) - Finlay, Samuel; MacDonald, Lucy; Tolusso, Barbara; Elmesmari, Aziza; Gigante, Maria Rita; Mario, Clara DI; Petricca, Luca; Filer, Andrew; Millar, Neal L; Gremese, Elisa; Mcinnes, Iain; Otto, Thomas; et al.
Abstract : Background: We hypothesise that synovial tissue macrophages (STM) are heterogeneous and mediate discrete pathogenic pathways that may underlie partial or absent therapeutic responses in RA patients. Better understanding of STMs will provide novel targets for re-instating synovial homeostasis. We have shown that the human synovium contains at least two major populations of STMs (CD206/MerTK neg and CD206/MerTK pos ) with transcriptomes suggesting different function. Objectives: To dissect the phenotypic and functional heterogeneity of STMs using single-cell transcriptomics and associated functional assays. Methods: The relative proportions of the two major populations of STMs were quantified in 64 RA synovial biopsies (including 26 from RA patients in sustained remission), and in 8 healthy synovial tissues by flow cytometry. To uncover STM phenotypes, single-cell RNA sequencing of STMs from healthy donors (n=4), active RA (n=7; DAS28 ≥5.1) and RA in remission (n=4; DAS28≤2.6) was performed with 10X Genomics. 21, 000 STMs were sequenced and analysed (Seurat). For functional analysis, CD206/MerTK neg and CD206/MerTK pos STMs were sorted from biopsies of active RA (n=15) and RA in remission (n=8). These were stimulated in vitro with LPS (to mimic activation by joint damage) or with LPS plus the MerTK agonist GAS6 to activate MerTK pos STMs; or co-cultured with FLS. Results: The synovium of healthy subjects and RA patients in remission contain predominantly CD206/MerTK pos STMs, whereas RA patients with any disease activity additionally contain substantial proportions of CD206/MerTK neg STMs. In active RA, the CD206/MerTK neg STMs produce TNF while CD206/MerTK pos STMs produce type I interferon following TLR4 activation. Interestingly, CD206/MerTK pos STMs from RA patients in remission showed a limited response to TLR stimulation, and their cytokine production was further inhibited by GAS6. This regulatory function of GAS6/MerTK was confirmed in macrophage-fibroblast co-culture assays: inhibition of MerTK in macrophages increased macrophage-induced cytokine production by FLS. STM single-cell transcriptomic analysis uncovered further STM heterogeneity in healthy, active RA and RA in remission (5 distinct subpopulations). These included three subpopulations that were not present in healthy and remission RA. These inflammatory subpopulations differ in their expression of surface receptors, spectrum of activated pathways and in their frequency in the synovium of patients with similar high DAS28. One of the subpopulations, characterised by increase metabolism, pro-inflammatory cytokines (e.g. IL-1β, BAFF) and chemokines, dominated in 3 out of 7 RA patients with active RA analysed; the second, characterised by high levels of MHC II and GPR receptors in 2 out of 7 patients while the third one characterised by high levels of alarmins (e.g. S100A8, 9 and 12) dominated in the remaining 2 inflamed RA synovia. Conclusion: Pathogenic diversity of inflammatory synovial tissue macrophage subpopulations may partially account for unpredictable clinical responses in RA. Identifying and targeting the predominant STM subpopulation may facilitate novel therapeutic development and eventually patient stratification. Acknowledgement: Versus Arthritis RACE20298 Disclosure of Interests: Samuel Finlay : None declared, Lucy MacDonald : None declared, Barbara Tolusso: None declared, Aziza Elmesmari: None declared, Maria Rita Gigante: None declared, Clara Di Mario: None declared, Luca Petricca: None declared, Andrew Filer: None declared, Neal L Millar: None declared, Elisa Gremese Consultant for: AbbVie, BMS, Celgene, Janssen, Lilly, MSD, Novartis, Sanofi, UCB, Roche, and Pfizer, Speakers bureau: BMS, Speakers bureau: Roche, Speakers bureau: AbbVie, BMS, Celgene, Janssen, Lilly, MSD, Novartis, Sanofi, UCB, Roche, and Pfizer, Iain McInnes Grant/research support from: AstraZeneca, Celgene, Compugen, Novartis, Roche, UCB Pharma, Consultant for: AbbVie, Celgene, Galvani, Lilly, Novartis, Pfizer, UCB Pharma, Thomas Otto: None declared, Stefano Alivernini Speakers bureau: BMS, Mariola Kurowska-Stolarska: None declared